Pemanfaatan Selenium WebDriver untuk Pengujian Regresi Aplikasi Berbasis Web - Sofani, Ratu Fairuz Hasna; idris, Moh (Universitas Samudra, 2024)
Software testing is an important stage in software development that aims to verify the performance and suitability of an application or system with user requirements. Software that is being developed will not avoid bugs because the software will continue to update and/or change the system, so regression testing is needed to ensure that the changes that made during the software development process is not affecting the functionality of the system that was running well before. In recent years, automated testing has become a popular and efficient method of performing software testing, especially on iterative regression testing. By using automation tools such as Selenium WebDriver, regression testing can be carried out thoroughly and does not take much time. Keywords: Software Testing, Regression Testing, Automation Testing, Selenium WebDriver